Changes in plasma 5-HT levels and equine leukocyte SERT expression in response to treadmill exercise. (June 2018) - D'Ascola, Angela; Bruschetta, Giuseppe; Zanghì, Gabriella; Campo, Salvatore; Medica, Pietro; Campana, Stefania; Ferlazzo, Guido; Gibbs, Bernhard F.; Ferlazzo, Alida Maria
Abstract: Serotonin (5-HT) is a neurohormone transported from plasma into platelets and leukocytes by a specific transporter (SERT). While it is known that the brain 5-HT system is modulated by physical exercise, the peripheral serotoninergic response to exercise is not yet fully elucidated. In particular, this study aimed to evaluate changes in plasma 5-HT levels and equine leukocyte SERT expression in response to treadmill exercise in untrained horses. Analyses were carried out pre- and post-treadmill exercise. 5-HT plasma levels were analysed by HPLC. Leukocytes and platelets were isolated to perform Real Time PCR for the evaluation of SERT mRNA levels. Western blot was conducted for the detection of SERT protein levels. The presence of SERT in leukocytes was analysed by flow cytometry. The functionality of SERT on leukocytes was investigated by using paroxetine as inhibitor of 5-HT reuptake. Results showed a significant decrease in SERT levels after exercise in both leukocytes and platelets and a significant increase in plasma 5-HT levels. Flow cytometry revealed that SERT is functional in one specific horse leukocyte subpopulation, still not identified, and paroxetine was able to block 5-HT reuptake into leukocytes. The exercise may have induced an increased mobilization of free-tryptophan and a release of 5-HT from the stores in the blood. High concentrations of plasma 5-HT could have caused a reduction in SERT expression affecting cellular 5-HT storage/uptake. The increase of cortisol levels after treadmill exercise was not significant. Exercise modulates the peripheral serotonin metabolism. More research is needed to assess its physiological implications. Highlights: Horse plasma serotonin, tryptophan and cortisol levels before and after exercise were investigated. A significant increase of plasma serotonin after treadmill exercise was detected. A significant decrease of equine platelet SERT levels after exercise was measured. A significant decrease of equine leukocyte SERT levels after exercise was detected. SERT is functional in one specific horse leukocyte subpopulation.